The Financial and Social Benefit of Small and Medium Enterprises: A Case Study of a Commercial Center in Diyala Governorate - Ahmed, Sanaa Sattar (International Journal of Psychosocial Rehabilitation, 2020)
Small enterprises are considered an effective development tool in creating new job opportunities for young people and raising their standard of living. Therefore, the application of research in one of these commercial centers, which is located in Baquba, Diyala Governorate Center, aims to answer the following question (What is the extent of the benefit achieved by small or medium enterprises with The private sector in terms of financial and social) The study relied on the descriptive and analytical approach, the study concluded that the commercial center provides job opportunities for young people between 25-30 individuals and allocates an amount estimated at (14,000,000) as wages for its workers, divided each according to the worker's specialization and academic achievement, which limits unemployment In the region and the recommendations presented by the research are to provide the means to facilitate the establishment of such projects because of their role in achieving financial benefit for youth and achieving social benefit as well. Therefore, the state must support these projects in particular and small and medium enterprises in general.